Testing for SARS-CoV-2 at the core of voluntary collective isolation: Lessons from the indigenous populations living in the Amazon region in Ecuador. (April 2021) - Ortiz-Prado, Esteban; Rivera-Olivero, Ismar A.; Freire-Paspuel, Byron; Lowe, Rachel; Lozada, Tannya; Henriquez-Trujillo, Aquiles R.; Garcia-Bereguiain, Miguel Angel; ,
Highlights: Self-isolation has been proposed as a strategy for SARS-CoV-2 control and prevention in indigenous communities. An increasing prevalence of SARS-CoV-2 infection was found among remote and isolated Waorani communities in the Amazonian region of Ecuador after two visits. Self-isolation failed to avoid either the outbreak or the spread of the COVID-19 among Waorani communities. High SARS-CoV-2 infection rates were found among Waorani groups. Abstract: Voluntary collective isolation has been proposed to be the best response to COVID-19 for indigenous populations. While the potential value of voluntary collective isolation is appealing, the feasibility of this approach needs empirical evidence to support it as the best response to protect indigenous communities from COVID-19. This paper describes our experience during SARS-CoV-2 surveillance among Waorani communities in the Ecuadorian Amazonian region, from June to September 2020. We found that self-isolation strategies failed to contain the spread of SARS-CoV-2 from main urban areas to remote and isolated comunities.